1997
DOI: 10.1524/zpch.1997.198.part_1_2.043
|View full text |Cite
|
Sign up to set email alerts
|

The Ice Bilayer on Pt(111): Nucleation, Structure and Melting

Abstract: H20/Pt(lll)-interface 12D-structure I Phase transition I Scanning tunneling microscopy The H20-adsorption on Pt(l 11) at 120 K-140 is investigated by temperature-variable scanning tunneling microscopy. At 140 the adsorption kinetics of the first bilayer is determined by heterogeneous nucleation at the upper side and the lower side of step edges as well as by homogeneous island nucleation on the terraces. Depending on the preparation conditions the bilayer exhibits three different phases. Phase I can be charact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
97
0

Year Published

1997
1997
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(102 citation statements)
references
References 22 publications
5
97
0
Order By: Relevance
“…Using a temperature programmed desorption (TPD) and spectroscopic methods (XPS, UPS), Sexton and Hughes, obtained the adsorption energy of water on Pt(111) is 0.412 eV [48]. However, for the case of (111) surface index, our result of the atop position as the most preferential adsorption site is in agreement with STM results by Morgenstern et al [23,49]. The weakest interaction strength of H2O/Pt(111) compared to Pt(100) and Pt(110) indicates the most unflavored water dissociation at the Pt(111) surface.…”
Section: Resultssupporting
confidence: 90%
“…Using a temperature programmed desorption (TPD) and spectroscopic methods (XPS, UPS), Sexton and Hughes, obtained the adsorption energy of water on Pt(111) is 0.412 eV [48]. However, for the case of (111) surface index, our result of the atop position as the most preferential adsorption site is in agreement with STM results by Morgenstern et al [23,49]. The weakest interaction strength of H2O/Pt(111) compared to Pt(100) and Pt(110) indicates the most unflavored water dissociation at the Pt(111) surface.…”
Section: Resultssupporting
confidence: 90%
“…26 -29 Although only a small amount of electron density of states around the Fermi level is present on the O atoms, the results illustrate that the water molecules from the adlayer closest to the metal surface can play an active role in electron transfer reactions and should not be considered as a simple dielectric but as a conductive medium. These results are also in agreement with the experimental observations of Morgenstern et al, 28 who reported that water adsorbed on Pt͑111͒ appears as an elevation to the STM and therefore must be capable of conducting electric current.…”
Section: Electronic Structure Around the Fermi Levelconductivity Osupporting
confidence: 92%
“…18,20 A number of other studies considering electron transfer through the interface have also indicated that a water layer on a metal surface possesses an apparent conductivity due to a mixing of oxygen electronic states with the d band of the metal substrate. 28 This experimentally observed phenomenon, for which there is still only a limited theoretical description, can only be modeled using first-principles simulation techniques.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…amorphous ice [18,19,20,21,22,8], premelted [23,24,25] and solid [26,27,28] surfaces and adsorbed overlayers. The correct description of such systems is in many cases beyond the computational capabilities of available ab initio methods.…”
Section: Introductionmentioning
confidence: 99%